Combined Effect of Deoxynivalenol (DON) and Porcine Circovirus Type 2 (Pcv2) on Inflammatory Cytokine mRNA Expression - Gu, Chao; Gao, Xiuge; Guo, Dawei; Wang, Jiacai; Wu, Qinghua; Nepovimova, Eugenie; Wu, Wenda; Kuca, Kamil (Toxins, 2021)
A host's immune system can be invaded by mycotoxin deoxynivalenol (DON) poisoning and porcine circovirus type 2 (PCV2) infections, which affect the host's natural immune function. Pro-inflammatory cytokines, IL-1β and IL-6, are important regulators in the process of natural immune response, which participate in inflammatory response and enhance immune-mediated tissue damage. Preliminary studies have shown that DON promotes PCV2 infection by activating the MAPK signaling pathway. Here, we explored whether the mRNA expression of IL-1β and IL-6, induced by the combination of DON and PCV2, would depend on the MAPK signaling pathway. Specific pharmacological antagonists U0126, SP600125 and SB203580, were used to inhibit the activities of ERK, JNK and p38 in the MAPK signaling pathway, respectively. Then, the mRNA expression of IL-1β and IL-6 in PK-15 cells was detected to explore the effect of the MAPK signaling pathway on IL-1β and IL-6 mRNA induced by DON and PCV2. The results showed that PK-15 cells treated with DON or PCV2 induced the mRNA expression of IL-1β and IL-6 in a time- and dose-dependent manner. The combination of DON and PCV2 has an additive effect on inducing the mRNA expression of IL-1β and IL-6. Additionally, both DON and PCV2 could induce the mRNA expression of IL-1β and IL-6 via the ERK and the p38 MAPK signal pathways, while PCV2 could induce it via the JNK signal pathway. Taken together, our results suggest that MAPKs play a contributory role in IL-1β and IL-6 mRNA expression when induced by both DON and PCV2.
Keywords: Animals; MAP Kinase Signaling System; IL-1β; deoxynivalenol; buněčné linie; PCV2; Circovirus; prasata; messenger RNA; Interleukin-6; MAPK; Cell Line; RNA, Messenger; Circoviridae Infections; Trichothecenes; Interleukin-1beta; Swine; interleukin-6; trichotheceny; interleukin-1beta; zvířata; IL-6; MAP kinasový signální systém; infekce viry čeledi Circoviridae